Glass Ceiling in Focus: A Comprehensive Bibliometric Review of Business and Management Studies - Mahat, Dipak (International Journal of Education, Management, and Technology, 2024)
The glass ceiling continues to impede women's progression into leadership roles within Business and Management Studies. Despite increased awareness of gender inequality, systemic challenges remain pervasive. This study aims to conduct a bibliometric review to elucidate the trends, key contributors, and geographical landscape related to the glass ceiling from 1999 to 2024. A systematic review methodology was employed, sourcing data from the Scopus database using the keyword "Glass Ceiling." The results indicate a significant uptick in publications post-2017, reflecting increased scholarly attention on gender inequality, influenced by movements such as MeToo. Influential authors, including Senthil Arasu Balasubramanian and Néstor Gandelman, were identified, with the United States leading in geographical contributions, followed by Australia and Spain. New themes such as the "glass cliff" and the unique challenges faced by African women emerged, highlighting the need for a broader focus on intersectionality in future research. The findings reveal an evolving research landscape surrounding the glass ceiling, emphasizing the necessity for interdisciplinary collaboration among scholars. These insights call for targeted initiatives to address barriers to women's leadership advancement. This study offers a comprehensive bibliometric analysis of the glass ceiling phenomenon in Business and Management Studies, charting the evolution of research trends and identifying key authors and geographical disparities. It provides a framework for future investigations into gender inequality in leadership.